Nanotechnology-Based Surface Plasmon Resonance Affinity Biosensors for In Vitro Diagnostics - Riccarda Antiochia; Paolo Bollella; Gabriele Favero; Franco Mazzei (International Journal of Analytical Chemistry)
In the last decades, in vitro diagnostic devices (IVDDs) became a very important tool in medicine for an early and correct diagnosis, a proper screening of targeted population, and also assessing the efficiency of a specific therapy. In this review, the most recent developments regarding different configurations of surface plasmon resonance affinity biosensors modified by using several nanostructured materials for in vitro diagnostics are critically discussed. Both assembly and performances of the IVDDs tested in biological samples are reported and compared.